The Effect of Training on the Notification of Sharp Instrument Injuries - Oğuz KARABAY; Gülsüme KAYA; Aziz ÖĞÜTLÜ (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2014)
Introduction: Healthcare workers can get several infectious factors from the health facilities they are working in and the patients they care for. These risks further increase especially during parenteral procedures. Sharp instrument injuries (SII) can cause transmission of blood-borne diseases to healthcare workers. The aim of this study was to evaluate the changes in the SII notifications after training given between January 2012 and June 2014. Materials and Methods: Initially, 2010-2012 basal values of the SII reports in Sakarya University Training and Research Hospital were analysed. Physicians, nurses, auxiliary health personnel and health care students participated to monthly training meetings as of January 2012. The importance of sharp instrument injuries and protection methods from SII and the steps to follow when these events occur were explained in these educational meeting sessions. The notifications of SII and exposure to bodily fluids before (2010-2012) and during the training (2012-2014) in Sakarya University Training and Research Hospital were retrospectively evaluated. Results: Thirty-nine (2.03%) SII notifications were reported before the training while 192 (3.35%) SII notifications were recorded after the training (p= 0.003). According to occupational groups, most SII notifications were observed in nurses (44.1%) while least notifications were seen in physicians (5.6%). Needle tip was the tool with which the most injuries occurred (72%). Participation rate to the training sessions was found 20% in physicians, 58% in nurses, and 57% in auxiliary health personnel. Conclusion: Training given to the healthcare workers positively affected SII notifications. It is concluded that physicians don’t pay enough attention to SII reports. We believe that knowledge and awareness about SIIs should be increased in the pregraduate period.